Paleoviral maintenance in a Holarctic Daphnia species complex, 2010-2012 ... - Taylor, Derek (NSF Arctic Data Center, 2017)
Daphniids are critical members of Holarctic freshwater ecosystems. However, little is known of their interactions with RNA viruses. These data represent sequence information supporting the hypothesis that a viral gene from a Phelobvirus-like RNA virus has been transferred into the genomes of common species of Arctic Daphnia. The gene is similar to the RNA-Dependent RNA polymerase (RDRP) gene of phleboviruses (Phenuiviridae). The data also contain mitochondrial sequence from the host to classify the lineage of Daphnia that contains each "fossil" virus. These data indicate, for the first time, that common species of Daphnia in the Arctic have been infected with RNA viruses. Moreover, the evidence indicates that viral genes may be maintained for a presently unknown host function. Because the paleoviruses represent a "captured" viral gene (RDRP) that is often used for the classification of RNA viruses, these data also provide a means of identifying and studying novel viruses and their present interactions in ...